Resourced based factors of competitiveness of agricultural enterprises = Zasobowe czynniki konkurencyjności przedsiębiorstw rolnych - Matyja, Małgorzata (Zielona Góra: Faculty of Economics and Management Press)
Among many different definitions of competitiveness it is difficult to pinpoint the most appropriate one. In the paper it was defined as the ability to be profitable by effective use of available resources. The profitability ratios (ROS, ROA, ROE and value index) were proposed as measures of competitiveness and resources were indicated as one of the group of factors that has an impact on it. Precisely, the purpose of the paper was to examine the relationship between selected resourced based factors and competitiveness of agricultural enterprises.
Keywords: konkurencyjność; zasoby; przedsiębiorstwa rolne; rentowność; korelacja; competitiveness; resources; agricultural enterprises; profitability; correlation